2013
DOI: 10.1080/02646838.2013.835795
|View full text |Cite
|
Sign up to set email alerts
|

A review of instruments to measure health-related quality of life and well-being among pregnant women

Abstract: Objective: To describe a rapid review of major health-related, electronic bibliographic databases, to identify pregnancy-specific measures of health-related quality of life and well-being. This paper details the range of available instruments, rather than aiming to critique their psychometric properties or indicate problem prevalence. Background: While many instruments are used to measure health and well-being in pregnant women, most are primarily designed for use with a generic population to quantify the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
0
12
1
Order By: Relevance
“…In the present study, economic and ecological factors were determined as the antecedents of the well-being concept not as its attributes. Another study defined well-being in low-risk pregnancy as the absence of any illness [69]. However, the present study showed that well-being can also be defined in HRP, where pregnant women suffer from a disorder of illness.…”
Section: Discussioncontrasting
confidence: 53%
“…In the present study, economic and ecological factors were determined as the antecedents of the well-being concept not as its attributes. Another study defined well-being in low-risk pregnancy as the absence of any illness [69]. However, the present study showed that well-being can also be defined in HRP, where pregnant women suffer from a disorder of illness.…”
Section: Discussioncontrasting
confidence: 53%
“…Since its development, the TPDS has been translated into English, Portuguese, Turkish, Spanish, and Bahasa Indonesia (e.g., apik & Pasinlioglu 2015). Morrell et al (2013) emphasized the fact that the TPDS was developed using focus-group interviews as a starting point, and a recent systematic review of self-report questionnaires of anxiety during pregnancy evaluated the TPDS as excellent in terms of its internal consistency and structural validity (Evans et al 2015). However, it was also concluded that data on hypothesis testing and construct validity was insufficient and data on reliability were not reported (Evans et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Pregnancy is a life phase when there is a greater focus on health and the potential for this focus to lead to improved health. 23 Moderate intensity physical activity during pregnancy is associated with improved mood and self-image; more sleep; more appropriate weight gain; improved muscle tone, strength and endurance; increased energy levels during labor and delivery and more rapid recovery following labor and delivery. 24 Currently there are limited published data investigating the relationship between exposure to green space and the physical activity levels of pregnant women.…”
Section: Introductionmentioning
confidence: 99%